APERTURA ECONóMICA E INTEGRACIóN REGIONAL ESTRATEGIAS COMPLEMETARIAS - Löwenthal, Paul (2015)
Trade liberalization is part of what LatinAmerica persues as economic development.It is also necessary to generate increased revenuestreams that would not only develop theinternational market but also local and this iswhere We should analyze the possible effectsof imports and exports in the region.